2013
DOI: 10.3171/2013.6.peds1383
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cerebellopontine angle and internal auditory canal tumors

Abstract: Object The aim in this study was to describe the clinical presentation, differential diagnosis, and risk for neurofibromatosis Type 2 (NF2) in pediatric patients presenting with cerebellopontine angle (CPA) and internal auditory canal (IAC) tumors. Methods The authors conducted a retrospective study at a tertiary care academic referral center. All patients with an age ≤ 18 years who had presented with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…In one large series [10] of pediatric CPA tumors, VSs also comprised the largest portion (60%), followed by meningioma (6%) and epidermoid cysts (5%), similar to adult population. [10,13,14] Likewise, Cunningham et al [15] reported that rate of VS is 86% on the basis of data obtained from a study with 115 pediatric lateral skull base lesions. However, in a study of Zúccaro and Sosa's [16] which consisted of 33 cases of pediatric CPA tumors, this rate was only 24%.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In one large series [10] of pediatric CPA tumors, VSs also comprised the largest portion (60%), followed by meningioma (6%) and epidermoid cysts (5%), similar to adult population. [10,13,14] Likewise, Cunningham et al [15] reported that rate of VS is 86% on the basis of data obtained from a study with 115 pediatric lateral skull base lesions. However, in a study of Zúccaro and Sosa's [16] which consisted of 33 cases of pediatric CPA tumors, this rate was only 24%.…”
Section: Discussionmentioning
confidence: 89%
“…[8] On the other hand, significant proportion of unilateral pediatric VSs, assessed as sporadic at the time of diagnosis, has been reported to be diagnosed with NF2 at a later stage in life. [10] The rate of VSs is 96% in patients with genetically detected NF2, taking into consideration both unilateral and bilateral tumors. [17] In their study that analyzed pediatric CPA tumors, Holman et al [10] reported that 6% of children with schwannoma showed NF2 trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a limited number of case reports of spontaneous intracranial schwannomas in children 1 2. Up to 40% of children with cerebellopontine angle tumours may be negative for neurofibromatosis type 2 2.…”
Section: Descriptionmentioning
confidence: 99%
“…At 36 months post-treatment, the patient exhibited no identifiable tumor enlargement. Within the literature, the treatment strategies for small VSs are varied, making it difficult for a neurosurgeon to decide the best course of action (4,7,8). In a study from the US, the strongest predictors of treatment modality were patient age and tumor size (3).…”
Section: Case Reportmentioning
confidence: 99%